DETERMINANTS OF CONCUMPTION BEHAVIOR AMONG STUDENTS - Ardiyanti, Novicha; Harnanik, Harnanik (Economic Education Analysis Journal, 2017)
This research aims to determine if there is influence of peer group, parents’ role, religiosity, financial literacy towards consumption behavior among the students of Economics Faculty, Semarang State University Academic Year 2013. The population in this research was the students of Economics Faculty Semarang State University Academic Year 2013. The number of the samples in this research was 250 students based on proportional random sampling technique. This research used quantitative approach. The method of data analysis useddescriptive analysis and path analysis.The result of the research based on Amos showed that the peer group influence towards consumption behavior was 34.5%, parents’ role towards consumption behavior was 12.7%, financial literacy towards consumption behavior was 12.7%, peer group towards financial literacy was 14%, parents’ role towards religiosity was 22.3%. Based on the result of the research, it can be concluded that there was influence of peer group, parents’ role, religiosity, financial literacy towards consumption behavior, whereas in peer group towards students’ financial literacy had no influence. The suggestionswere: (1) the students should minimize the conformity or interaction level with their friends who cause negative impact and the parents should keep controlling the students’ consumption behavior naturally.